1, 2, 3-Triazole amine as directing group in promoting catalytic oxidative C–H olefination under aerobic conditions. Issue 22 (2nd June 2016) - Ye, Xiaohan; Zhang, Yanwei; He, Ying; Shi, Xiaodong
Abstract: A practical ortho C–H olefination of phenyl acetic acid derivatives was achieved with a 1, 2, 3-triazole auxiliary directing group. Good to excellent yields were achieved with O2 as terminal oxidant. Other bidentate directing groups, such as 8-aminoquinoline, gave poor reactivity under this aerobic condition, highlighting the unique reactivity of triazole in promoting C–H activation. Graphical abstract: